2021
DOI: 10.1007/s11211-021-00369-w
|View full text |Cite
|
Sign up to set email alerts
|

Can Personality Traits Predict Depression during the COVID-19 Pandemic?

Abstract: The emotional costs of the COVID-19 pandemic have raised concerns among clinicians and scholars. The goal of the current study was to test whether or not neuroticism, conscientiousness, and personal belief in a just world are associated with depression during the COVID-19 pandemic. Moreover, the contribution of neuroticism and conscientiousness was assessed over and above demographic variables and COVID-19 perceptions, and the unique contribution of personal belief in a just world was evaluated beyond all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 69 publications
4
11
0
Order By: Relevance
“…The study’s findings provide further support for the role of neuroticism, which can be associated with mental health problems (Norton & Paulus, 2017 ). Additionally, consistent with recent studies (Nudelman et al, 2021 ; Modersitzki et al, 2020 ), the present study’s findings indicated that neuroticism was one of the risk factors associated with the mental health problems during the COVID-19 pandemic. Additionally, healthy emotionality may play a buffering role against the fear of the effect of COVID-19 on mental health problems.…”
Section: Discussionsupporting
confidence: 92%
“…The study’s findings provide further support for the role of neuroticism, which can be associated with mental health problems (Norton & Paulus, 2017 ). Additionally, consistent with recent studies (Nudelman et al, 2021 ; Modersitzki et al, 2020 ), the present study’s findings indicated that neuroticism was one of the risk factors associated with the mental health problems during the COVID-19 pandemic. Additionally, healthy emotionality may play a buffering role against the fear of the effect of COVID-19 on mental health problems.…”
Section: Discussionsupporting
confidence: 92%
“…We found that neuroticism could significantly negatively predict ER strategies and positively predict depression and NSSI behavior, which is consistent with the findings of Nudelman et al [ 31 ] and Shukla et al [ 32 ]. High neuroticism and self-awareness means emotional instability and poor emotional regulation, which is related to a high level of depression and anxiety.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, PBJW protected university students' life satisfaction and strengthened their justice-related university work behaviors. The current evidence during the COVID-19 pandemic 43 and results from other studies 3 , 30 , 122 , 123 support the robustness of belief in a just world.…”
Section: Discussionsupporting
confidence: 78%
“…Based on empirical findings 43 , PBJW could reduce the risk of stress-induced negative emotions and the development of depression due to the COVID-19 pandemic and increase well-being.…”
Section: Introductionmentioning
confidence: 99%